A Writable Polypeptide–DNA Hydrogel with Rationally Designed Multi‐modification Sites. Issue 9 (26th August 2014) - Li, Chuang; Chen, Ping; Shao, Yu; Zhou, Xu; Wu, Yuzhou; Yang, Zhongqiang; Li, Zhibo; Weil, Tanja; Liu, Dongsheng
Abstract : A polypeptide‐DNA hydrogel is prepared by employing the "X"‐shaped DNA assembling structure as crosslinker. The hydrogel can be modified with multifunctional components (here fluorescent molecules as a model) and possesses excellent self‐healing and thixotropic properties, enabling the direct‐writing of arbitrary 3D structures. This study provides a simple, universal strategy for the assembly of functionalized hydrogels.